(untitled) (Economics and region, 2025)
The article proves that the concept of Slow Food involves not only the formation of a conscious attitude towards food, but also contributes to the achievement of sustainable development goals, emphasizing environmental sustainability, social justice and the preservation of the nation’s cultural heritage. This approach combines concern for the environment with support for local communities, ensuring their economic stability and development. Slow Food helps to strengthen the connection between consumers and producers, forming a responsible society that values ​​local traditions, natural resources and gastronomic diversity. An analysis of consumer trends in the restaurant business was carried out, namely: the key factors that determine the choice of consumers when visiting restaurants were studied; and the level of interest in healthy eating, environmental and ethical aspects of food consumption was also determined. The level of awareness of the Slow Food concept was assessed by studying the perception of the main principles of Slow Food among different categories of consumers and identifying key barriers and incentives for popularizing the concept among the mass consumer. The factors that influence the choice of restaurant businesses were identified and the willingness of consumers to pay for dishes prepared from local, environmentally friendly ingredients was assessed. Recommendations were developed to substantiate the Slow Food concept, in particular, proposals were made for effective methods of popularizing the principles of Slow Food among consumers; communication channels and marketing tools were identified that will help attract the target audience. The need to adapt Slow Food to regional characteristics and culinary traditions was substantiated. The study allowed for a comprehensive assessment of the current state of development of the Slow Food concept in Ukraine, to identify potential barriers and opportunities for its adaptation in the restaurant industry, and to formulate practical recommendations for its implementation. The results of the study will contribute to the development of effective marketing approaches for adapting the Slow Food concept in the restaurant sector, which will allow improving the quality of food, developing local producers, and strengthening the environmental responsibility of business.